2006
DOI: 10.1002/ps.1303
|View full text |Cite
|
Sign up to set email alerts
|

Organic amendments affecting sorption, leaching and dissipation of fungicides in soils

Abstract: Metalaxyl and tricyclazole are two fungicides widely used in Spain in vineyard and rice crops respectively. In this study an investigation has been made of the effect of three organic amendments [two commercial amendments, solid fertiormont (SF) and liquid fertiormont (LF), and a residue from the olive oil production industry, alperujo (OW)] on fungicide fate in soils. Changes in soil porosity on amendment were studied by mercury intrusion porosimetry, sorption-desorption studies were performed by the batch eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 31 publications
(42 reference statements)
7
38
1
5
Order By: Relevance
“…Data revealed that adsorption of flubendiamide (Table 4) was higher in organic manure-treated soil than without organic manure-treated soil. Similar results were reported by Fernandes et al (2006). The dynamics of pesticides in soil was greatly affected by the varying physical and chemical properties of the soil, especially the organic matter and clay content as reported by Li et al (2003), Gajbhiye and Gupta (2001) and Beyer et al (1996).…”
Section: Resultssupporting
confidence: 90%
“…Data revealed that adsorption of flubendiamide (Table 4) was higher in organic manure-treated soil than without organic manure-treated soil. Similar results were reported by Fernandes et al (2006). The dynamics of pesticides in soil was greatly affected by the varying physical and chemical properties of the soil, especially the organic matter and clay content as reported by Li et al (2003), Gajbhiye and Gupta (2001) and Beyer et al (1996).…”
Section: Resultssupporting
confidence: 90%
“…The dynamics of pesticides in soil was greatly influenced by the varying physical and chemical properties of the soil, especially the organic matter and clay content (Li et al 2003). The data reveals that adsorption of tricyclazole (Table 3) was high in FYM-amended soils than without amendment, and similar results were reported by Fernandes et al (2006). The increase in adsorption percent of tricyclazole in amended soils may be related to the adsorption of the tricyclazole to the soil by increasing the available sorption sites.…”
Section: Resultssupporting
confidence: 86%
“…The main structural consequence is the progressive contraction of the allophane aggregates associated with closure of the mesopores. In the literature (Fernandes et al 2006), it has been shown that adding organic matter reduced soil porosity, mainly via a reduction in the largest pore size studied (10-100 μm). Similar results were obtained by Albarran et al (2004).…”
Section: Change In Soil Porosity During the Incubation Of Organic Mattermentioning
confidence: 99%